Bentuk-Bentuk Partisipasi Orang Tua Anak Usia Dini dalam Program PAUD di Kabupaten Konawe - Saasa; Untung (DIALEKTIKA: Jurnal Ilmiah Pendidikan Bahasa, Sastra, dan Matematika, 2015)
This study aims to analyze the forms of early childhood parents’ participation on education of early childhood program in Konawe regency. The forms of participation were analyzed with the approach of the participation concept, i.e. the participation of the planning, implementation, and evaluation stages. This study used a qualitative research method, which aims to analyze the phenomena, events, social activities, thinking people individually or in groups on the participation of parent’s early childhood. Based on the research objectives, so obtained the results of research, that the percentage participation rate of early childhood parents at the planning stage, the implementation stage, and the stage of monitoring and evaluations showed that 63 respondents (13%) high participated, 163 respondents (35%) medium participated, and 244 respondents (52%) low participated. Those mean that overall early childhood parents had fairly low levels of education of early childhood program. These findings did not mean that they did not have role at all in development of education of early childhood program. Only, on average, their participation in the three forms of participation described above was still quite low.